Rancang Bangun Smart Door Lock Berbasis Iot dan Recording Data Pada Firebase - M. Adonis; Slamet Winardi (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
Smart Door Lock is a development of a conventional manual home door lock or padlock. This study aims to create alternative technology at home by utilizing available lock technology. This study uses an Arduino Uno Microcontroller as the brain of the solenoid and as a power supply for the fingerprint scanner, and an esp 32 microcontroller as a tool for sending fingerprint data to firebase. The fingerprint scanner is run using the Arduino Ide to add fingerprints. Arduino programming is done using the Arduino IDE. The results of the study are described in the form of designing an automatic home door lock using a fingerprint scanner and Arduino as a solenoid control. The fingerprint data results will be visible in firebase